Alzheimer’s disease therapeutics targeted to the control of amyloid precursor protein translation: Maintenance of brain iron homeostasis - Bandyopadhyay, Sanghamitra (2014)
The neurotoxicity of amyloid beta (Aβ), a major cleavage product of the amyloid precursor protein (APP), is enhanced by iron, as found in the amyloid plaques of Alzheimer’s disease (AD) patients. By contrast, the long-known neuroprotective activity of APP is evident after α-secretase cleavage of the precursor to release sAPPα, and depends on the iron export actions of APP itself. The latter underlie its neurotrophic and protective effects in facilitating the homeostatic actions of ferroportin mediated-iron export. Thus APP-dependent iron export may alleviate oxidative stress by minimizing labile iron thus protecting neurons from iron overload during stroke and hemorrhage. Consistent with this, altered phosphorylation of iron-regulatory protein-1 (IRP1) and its signaling processes play a critical role in modulating APP translation via the 5′ untranslated region (5′UTR) of its transcript. The APP 5′UTR region encodes a functional iron-responsive element (IRE) RNA stem loop that represents a potential target for modulating APP production. Targeted regulation of APP gene expression via the modulation of 5′UTR sequence function represents a novel approach for the potential treatment of AD since altering APP translation can be used to improve both the protective brain iron balance and provide anti-amyloid efficacy. Approved drugs including paroxetine and desferrioxamine and several novel compounds have been identified that suppress abnormal metal-promoted Aβ accumulation with a subset of these acting via APP 5′UTR-dependent mechanisms to modulate APP translation and cleavage to generate the nontoxic sAPPα.